Effect of primaquine dose on the risk of recurrence in patients with uncomplicated Plasmodium vivax - WorldWide Antimalarial Resistance Network (WWARN) Vivax Primaquine Dosing Efficacy, Tolerability and Safety Study Group (2024)
Funding Australian National Health and Medical Research Council, Bill & Melinda Gates Foundation, and Medicines for Malaria Venture. Copyright © 2023 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license. Published by Elsevier Ltd.. All rights reserved.